Comparison of Chevron and Scarf osteotomies in hallux valgus correction: Functional and radiographic outcomes - Oikawa, Hugo; Baptista, Eric Zaneti Teixeira (Journal of the Foot & Ankle, 2025)
Objective: To compare the functional and radiographic outcomes between Chevron and Scarf osteotomies in hallux valgus correction. Method: A systematic review was conducted in the PubMed/MEDLINE, SciELO, Lilacs, and Embase databases from 2004 to 2024. Inclusion criteria included clinical trials and observational studies that directly compared both techniques. Results: Both osteotomies showed similar effectiveness in improving functional scores (AOFAS) and correcting hallux valgus and intermetatarsal valgus angles. Chevron osteotomy was more indicated in mild to moderate deformities, while Scarf osteotomy showed greater stability and versatility in severe deformities. Conclusion: Both osteotomies are effective, with specific advantages. The surgical choice must be individualized. Level of Evidence Level I; Systematic Review